Experimental investigation of thermal comfort performance of a radiant wall and ceiling panel system - Dogan, Ahmet; Kayaci, Nurullah; Demir, Hakan; Sevindir, Mustafa Kemal (YILDIZ TECHNICAL UNIV, 2022)
The number of radiant heating-cooling systems in building applications is increasing it is be-cause of low energy consumption, low operating temperature and high values they provide in terms of working compatibility with renewable energy sources. In this study, ground source heat pump integrated radiant panels installed on the wall and suspended ceiling of the office room in Yildiz Technical University Science and Technology Application and Research Centre were experimentally examined in terms of thermal comfort according to the relevant stan-dards. Vertical air temperature differences and mean radiant temperatures were investigated. The mean air temperature differences at 0.1 m and 1.7 m were found to be 3,9 oC 2.9 oC 3.5 oC, 3.1 oC and 3.4 oC on average for the five different stands, respectively. PMV and PPD values were found to be 0.78 and 18.9% for February 12 (Case 1), 0.36 and 8.4% for February 13 (Case 2), respectively. In the experiment carried out under the conditions of Case 2, while the com-fort conditions were provided in almost all of the day, the desired comfort conditions could not be achieved in Case 1 after 11 am.
Keywords: GSHP; Heat Pump; Radiant Systems; Thermal Comfort; Wall and Ceiling Heating; HEAT-TRANSFER; COOLING SYSTEMS; FLOOR; ENERGY; ROOM; Thermodynamics